Review: elimination of bacteriophages in whey and whey products - Atamer, Zeynep; Samtlebe, Meike; Neve, Horst; Heller, Knut J.; Hinrichs, Joerg (Frontiers in Microbiology, 2013)
As the cheese market faces strong international competition, the optimization of production processes becomes more important for the economic success of dairy companies. In dairy productions, whey from former cheese batches is frequently re-used to increase the yield, to improve the texture and to increase the nutrient value of the final product. Recycling of whey cream and particulated whey proteins is also routinely performed. Most bacteriophages, however, survive pasteurization and may re-enter the cheese manufacturing process. There is a risk that phages multiply to high numbers during the production. Contamination of whey samples with bacteriophages may cause problems in cheese factories because whey separation often leads to aerosol-borne phages and thus contamination of the factory environment. Furthermore, whey cream or whey proteins used for recycling into cheese matrices may contain thermo-resistant phages. Drained cheese whey can be contaminated with phages as high as 109 phages per mL. When whey batches are concentrated, phage titers can increase significantly by a factor of 10 hindering a complete elimination of phages. To eliminate the risk of fermentation failure during recycling of whey, whey treatments assuring an efficient reduction of phages are indispensable. This review focuses on inactivation of phages in whey by thermal treatment, ultraviolet (UV) light irradiation and membrane filtration. Inactivation by heat is the most common procedure. However, application of heat for inactivation of thermo-resistant phages in whey is restricted due to negative effects on the functional properties of native whey proteins. Therefore an alternative strategy applying combined treatments should be favoured - rather than heating the dairy product at extreme temperature/time combinations. By using membrane filtration or UV treatment in combination with thermal treatment, phage numbers in whey can be reduced sufficiently to prevent subsequent phage accumulations.